4th Equation of Motion. Start with the 1st Equation: ?x =?(vi vf)?tSolve for ?t ? 2 ?x = (vi vf) ?t ?t = (2 ?x)/(vi vf). 4th Equation of Motion. Substitute the expression for ?t into the 2nd Equation:vf = vi a?tvf = vi a(2?x/(vi vf)vf ? vi = a (2?x/(vi vf) (vf ? vi)(vf
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.